2017
DOI: 10.1021/acs.macromol.6b02675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Myrcene-Based Polymers and Styrene Block and Statistical Copolymers by SG1 Nitroxide-Mediated Controlled Radical Polymerization

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 112 publications
6
73
0
Order By: Relevance
“…On the other hand, all poly(S-co-Fa) samples were white powders. The catalyst productivity decreased with an increase of the cases of styrene/β-myrcene and styrene/farnesene copolymerization, respectively, entries 4-10 and entries [13][14][15][16][17]; this is consistent with the fact that 1 is poorly active towards β-myrcene and farnesene homopolymerization (entries 1-2 and 11-12). On the other hand, as the [terpene] 0 /[St] 0 feed ratio was raised, the terpene content in the resulting copolymers increased as expected; thus, a wide range of compositions was obtained (My content = 5.6-30.8 mol % and Fa content = 1.5-9.8 mol %).…”
Section: Copolymerizations Of Styrene With β-Myrcene and Farnesenesupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, all poly(S-co-Fa) samples were white powders. The catalyst productivity decreased with an increase of the cases of styrene/β-myrcene and styrene/farnesene copolymerization, respectively, entries 4-10 and entries [13][14][15][16][17]; this is consistent with the fact that 1 is poorly active towards β-myrcene and farnesene homopolymerization (entries 1-2 and 11-12). On the other hand, as the [terpene] 0 /[St] 0 feed ratio was raised, the terpene content in the resulting copolymers increased as expected; thus, a wide range of compositions was obtained (My content = 5.6-30.8 mol % and Fa content = 1.5-9.8 mol %).…”
Section: Copolymerizations Of Styrene With β-Myrcene and Farnesenesupporting
confidence: 71%
“…Syndioselective copolymerization of styrene with small amounts of a second monomer is one of the most common ways to tune the properties of sPS, and thus to improve its processability [9][10][11]. A few examples of styrene-myrcene polymers have already been reported, mostly via anionic or radical copolymerizations [12][13][14]. To our knowledge, only one paper has addressed the coordination copolymerization of styrene with β-myrcene (My) in the presence of the ternary system Cp * La(BH 4 ) 2 (THF) 2 /nBuEtMg/AliBu 3 , affording poly(S-co-1,4-trans-My) containing high amounts of myrcene (66-96 mol %) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Myrcene has been copolymerized with monomers typically used for thermoplastics like α‐methyl‐ p ‐methylstyrene and poly(lactic acid) by anionic polymerization, and more recently copolymerized with GMA and styrene by NMP . Far has been homopolymerized by ionic polymerization, but polymerization by RDRP has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early work by David presented emulsion copolymerization of styrene/methyl methacrylate and myrcene initiated by 2,2‐azobisisobutyronitrile, wherein a higher molecular weight (20 000 Da) but a lower conversion rate (5–13%) was obtained. In the last 3 years, additional works initiated by free radicals have been investigated . However, those studies revealed that free radical polymerization did not produce ideal results as they encountered issues such as longer reaction time (>15 h), uncontrollable microstructure, and unsatisfactory conversion rate (only up to 80%) .…”
Section: Introductionmentioning
confidence: 99%